Development of method of determination of current status of the cardiovascular and respiratory systems for sportsmen - Олейник [Olejnik N.], М. О.; Чибісов [Chibisov V.], В. І.; Рейдерман [Reiderman Yu.], Ю. І.; Скрипченко [Skripchenko I.], І. Т.; Чередник [Cherednik Ye.], Є. О. (Slobozhanskyi Herald of Science and Sport, 2012)
The technique of the test determine the physical status of the athlete. At the basis of the test evaluation of the cardiovascular and respiratory systems. Resonance problem solved objectively grouping as their body to determine their functional ability to work to overcome the problem of physical activity and the admissibility of work, including to overcome stress during exercise and physical training in a mode on-line. Solutions to these problems and gives a survey of the individual receiving the results of the determining parameters